FC081: Cholinesterase Inhibitors and Kidney Function Decline in Patients with Alzheimer's Dementia. (3rd May 2022) - Xu, Hong; Garcia-Ptacek, Sara; Bruchfeld, Annette; Fu, Edouard; Darreh Shori, Taher; Lindholm, Bengt; Eriksdotter, Maria; Jesus Carrero, Juan
Abstract: BACKGROUND AND AIMS: Preclinical evidence shows that activation of the cholinergic anti-inflammatory pathway (CAP) may have direct and indirect beneficial effects on the kidney. Cholinesterase inhibitors (ChEIs) are specific Alzheimer's dementia (AD) therapies that block the action of cholinesterases and activate CAP. This study explores a plausible effect of ChEIs on slowing kidney function decline. METHOD: Observational study with a landmark design of patients with incident AD from the Swedish Dementia Registry (SveDem) 2007–2018 with complete extraction of routine serum creatinine tests from the Stockholm CREAtinine Measurements (SCREAM) registry to evaluate estimated glomerular filtration rate (eGFR) over time. Patients starting on ChEI within 90 days of an AD diagnosis were compared to patients with AD not receiving ChEI. The primary study outcome was CKD progression, defined as the composite of a sustained eGFR decline of >30% from baseline, initiation of kidney replacement therapy or death attributed to kidney disease. Secondary outcome was death. Inverse probability of treatment weighting Cox models were used to estimate hazard ratios, balancing 45 confounders. RESULTS: We included 11 898 incident patients, of whom 6803 started on ChEI and 5095 did not. Mean age was 80 years, 64% were women and mean baseline eGFR was 68 mL/min/1.73 m 2 . After weighting, and during median follow-up time of 3.0 (IQR 1.3–4.5) years, 1231 events of CKD progression occurred, along with 5691 deaths. Compared to noninitiators, ChEI use was associated with a 18% lower risk of CKD progression [adjusted hazards ratio (aHR) 0.82; 95% confidence interval (95% CI) 0.70–0.96] and a 21% lower risk of death ( aHR 0.79; 0.72–0.86). Results were consistent across subgroups of age, sex, and across ChEI subclasses and after accounting for competing risks. CONCLUSION: In routinely cared patients with incident AD diagnosis, use of ChEI (versus no-use) was associated with lower risk of CKD progression and death, lending support to the role of CAP activation on preservation of kidney function.